La polémica Kuhnn-Popper. Enrique Suárez-Iñiquez - Suárez-Iñiquez, Enrique; Dávila Aldas, Francisco R (Méx., D.F : UNAM, 1992)
Repaso entre la polémica Kunn-Popper sobre la estructura de la revolución científica
Keywords: TEORIA; CIENCIAS SOCIALES; KHUN, THOMAS SAMUEL; POPPER, KARL RAIMUND